Variation in quality of primary-care services in Kenya, Malawi, Namibia, Rwanda, Senegal, Uganda and the United Republic of Tanzania - Margaret E. Kruk; Adanna Chukwuma; Godfrey Mbaruku; Hannah H. Leslie (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Objective: To analyse factors affecting variations in the observed quality of antenatal and sick-child care in primary-care facilities in seven African countries. Methods: We pooled nationally representative data from service provision assessment surveys of health facilities in Kenya, Malawi, Namibia, Rwanda, Senegal, Uganda, and the United Republic of Tanzania (survey year range: 2006-2014). Based on World Health Organization protocols, we created indices of process quality for antenatal care (first visits) and for sick-child visits. We assessed national, facility, provider and patient factors that might explain variations in quality of care, using separate multilevel regression models of quality for each service. Findings: Data were available for 2,594 and 11 402 observations of clinical consultations for antenatal care and sick children, respectively. Overall, healthcare providers performed a mean of 62.2% (interquartile range, IQR: 50.0 to 75.0) of eight recommended antenatal care actions and 54.5% (IQR: 33.3 to 66.7) of nine sick-child care actions at observed visits. Quality of antenatal care was higher in better-staffed and -equipped facilities and lower for physicians and clinical officers than nurses. Experienced providers and those in better-managed facilities provided higher quality sick-child care, with no differences between physicians and nurses or between better- and less-equipped clinics. Private facilities outperformed public facilities. Country differences were more influential in explaining variance in quality than all other factors combined.
Keywords: 330; antenatal care; sick-child care; quality of care